Effect of Al content on microstructures and properties of Fe1.25CoCrNi1.25Alx high-entropy alloys. Issue 8 (24th May 2021) - Li, Chunyan; Lu, Yu; Li, Xinling; Zhao, Zhenxiang; Kou, Sheng-Zhong
Abstract : The effect of Al content on microstructures and properties of Fe1.25 CoCrNi1.25 Al x ( x = 0.1, 0.25, 0.4) high-entropy alloys was studied. The alloys arecomposed of a single-phase face-centered cubic solid solutionand do not change with the change of Al content. The tensile yield strength of as-cast alloys is below 200 MPa, and the elongation is above 55%. After cold-rolling and annealing, the strength and hardness increase with the increase of Al content. The comprehensive mechanical properties of the alloy with x = 0.25 reach the best. The texture composition of Fe1.25 CoCrNi1.25 Al0.4 gradually changes from 100 <001> to 110 <101> after cold-rolling and annealing. Trace Al is beneficial to improve the corrosion resistance of the alloys.